Bond between high strength concrete with recycled coarse aggregate and reinforcing bars. (May 2014) - Kim, S. H.; Lee, S. H.; Lee, Y. T.; Hong, S. U.
Abstract : Recently, natural aggregate resource depletion are being raised due to the pollution issues regarding the construction waste generated during demolition of building deterioration and the supply issues of aggregates. Recycled aggregates are being used as a solution to these issues, but the quality and durability/structural performance issues are the restriction of application. This study conducted a comparative evaluation of bond behaviour according to the reinforcing bar type and substitution rate of recycled coarse aggregate mixed with high strength concrete. That was carried out to verify the applicability of recycled coarse aggregate concrete as a structural member. Seventy-two specimens were manufactured with variables of recycled aggregate substitution rate (0, 30, 50 and 100%), reinforcing bar arrangement direction and reinforcing bar types. The bondstress and the slip relation of reinforcing bar and concrete in high strength concrete using recycled aggregate were found to have little influence on the reinforcing bar arrangement direction, location and substitution rate.